Reproductive life histories: can incremental dentine isotope analysis identify pubertal growth, pregnancy and lactation? - Corinne Feuillâtre; Julia Beaumont; Fadil Elamin (Taylor & Francis Group, 2022)
Background There are few reliable osteological indicators to detect parity or infer puberty in skeletal remains. Nitrogen (δ15N) and stable carbon (δ13C) isotope ratios in human tissues can be affected by metabolically unbalanced states engendered by pregnancy or rapid growth, offering potential biomarkers. Aim This pilot study explores the potential of incremental dentine-collagen isotope ratio analysis to identify puberty and gestation. Subjects and methods Incremental dentine δ15N and δ13C profiles were produced by analysing third molars extracted as part of dental treatment of 10 individuals living in Sudan. Demographic and anthropometric data at the time of tooth extraction was available. Medical histories were unknown. Results Isotopic signatures potentially related to pubertal growth, with an average δ15N reduction of 0.78 ± 0.29‰, are indicated. Six isotopic signals suggestive of pregnancy, with an average δ15N decrease of 0.48 ± 0.22‰, are also observed. The timing, speed and amplitude of post-partum δ15N patterns seemingly infer infant feeding practices and maternal nutritional status. Conclusion This pilot study highlights the potential of incremental dentine isotope analysis for the reconstruction of early reproductive histories in skeletal remains. However, controlled studies with a larger human cohort are needed to validate these findings, establish isotopic signals linked to puberty and lactation, and improve chronology accuracy.